(3ebOeI aj HMhK GdYedjGJ (B/s - (3MeOGf, aJMi Ndjds ((3YeGf(B: s (3OGQ hGFd ddfTQ h GdJhRjY(B, s, 2004)
(3eaghe HMhK GdYedjGJ hJWhQgG GdJGQjNj, HQeLI GdNWjI, GdfehPL GdebGHd, JMdjd GdMSGSjI, eTGcd Gdfbd, eTGcd GdJYjjf, THcGJ GdCYeGds
(3HHdjhZQGajG(B: (3U(B.213s
Keywords: (3GdHQeLI GdNWjIs; (3HMhK GdYedjGJs